2011
DOI: 10.1590/s0047-20852011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre fissura e perfil antropométrico em dependentes de crack

Abstract: rESUMo objetivo: Verificar a variação da fissura de dependentes de crack no decorrer da internação e a associação com perfil antropométrico. Métodos: Trata-se de uma pesquisa quantitativa com delineamento transversal (n = 30). Avaliaram-se o perfil de consumo de substâncias psicoativas; dados sociodemográficos; variáveis antropométricas (peso, estatura, índice de massa corporal, relação cintura-quadril, perímetros, dobras cutâneas e diâmetro ósseo); e fissura avaliada por meio do Cocaine Craving Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
2
6
0
9
Order By: Relevance
“…Regarding abstinence from crack, it was identified that, the shorter the period, the greater the craving for the drug, thus, those CAPS users who report shorter lengths of abstinence have higher scores for craving. These findings are similar to those of other studies that indicate that, the more recent the crack use, the greater the craving (17) . The association between length of abstinence and craving can be used when treating crack users, in order to motivate them to deal with a more intense desire at the beginning of the detoxification process, as they will be aware that this is a transitory stage (17) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding abstinence from crack, it was identified that, the shorter the period, the greater the craving for the drug, thus, those CAPS users who report shorter lengths of abstinence have higher scores for craving. These findings are similar to those of other studies that indicate that, the more recent the crack use, the greater the craving (17) . The association between length of abstinence and craving can be used when treating crack users, in order to motivate them to deal with a more intense desire at the beginning of the detoxification process, as they will be aware that this is a transitory stage (17) .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to those of other studies that indicate that, the more recent the crack use, the greater the craving (17) . The association between length of abstinence and craving can be used when treating crack users, in order to motivate them to deal with a more intense desire at the beginning of the detoxification process, as they will be aware that this is a transitory stage (17) . In this study, it was observed that cravings diminished with length of abstinence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Em relação a esse parâmetro, os resultados do presente estudo vão ao encontro aos de Cowan e Devine 8 , que mostram média de CC ≥ 94 cm, o que representa aumento dos riscos cardiovasculares. Observa-se que muitos estudos 18,20,22 que realizaram avaliação do estado nutricional não utilizaram a medida da CC de forma isolada, em sua maioria os estudos utilizaram a relação cintura-quadril (RCQ).…”
Section: Discussionunclassified
“…Na literatura, poucos estudos avaliam a composição corporal de indivíduos adultos usuá-rios de drogas. Desses, a maioria realiza a medida de dobras cutâneas para avaliar esse parâmetro 20,22 . Entretanto, Willhelm et al 21 avaliaram a composição corporal por meio de BIA e encontraram, na alta hospitalar, média de %GC de 20,15 ± 4,96.…”
Section: Discussionunclassified